Evaluation of insecticidal properties of botanicals for sustainable management of sucking pests of horticultural crops. (7th November 2022) - Prasannakumar, Nagalapura Ramakrishnappa; Rao, Vala Keshava; Jyothi, Nagendraiah; Saroja, Sarikonda; Lokesha, Ankanahalli Naranayanashetty; Ramkumar, Govindaraju
Abstract: Aphids, thrips, whiteflies, mealy bugs and mites could cause significant yield losses in horticultural crops. Many synthetic chemicals highly hazardous to non‐target organisms and the environment are in use in their management. Botanicals are ideal for safe sustainable pest management by keeping synthetic chemical use at a minimum. We studied the insecticidal properties of three botanicals viz., Annona squamosa, Ricinus communis and Sapindus mukorossi seed extracts against sucking pests viz., aphids ( Aphis gossypii and Aphis craccivora ) on okra ( Abelmoschus esculentus ) and bittergourd ( Momordica charantia ), thrips ( Scirtothrips dorsalis ) on chilli ( Capsicum frutescens ), whiteflies ( Bemisia tabaci ) on eggplant ( Solanum melongena ), mealy bugs ( Maconellicoccus hirsutus ) on betel vine ( Piper betle ) and mites ( Tetranychus urticae ) on eggplant ( Solanum melongena ) under laboratory conditions. The bioassay showed that A. squamosa seed extract has potent insecticidal properties on all sucking pests, except T. urticae . Though S. mukorossi seed extract exhibited no insecticidal property, had a significant acaricidal property. A. squamosa and S. mukorossi seed extracts will therefore be additional botanicals for use in organic farming for managing the sucking pests effectively.